Ribosomal protein S19 gene mutations in patients with diamond-blackfan anemia and identification of ribosomal protein S19 pseudogenes - Cmejla, R; Blafkova, J; Stopka, T; Zavadil, J; Pospisilova, D; Mihal, V; Petrtylova, K; Jelinek, J (Blood cells, molecules & diseases, 2000)
Diamond-Blackfan anemia (DBA) is a rare congenital pure red cell hypoplasia characterized by a selective defect of erythropoiesis with a normochromic macrocytic anemia and reticulocytopenia often accompanied by various congenital anomalies. The critical region responsible for the pathogenesis of DBA has been mapped in some patients to chromosome 19q13.2 (P Gustavsson, E Garelli, N Draptchinskaia, et al. Am. J. Hum. Genet. 63:1388-1395, 1998) and the gene encoding ribosomal protein S19 (RPS19) is believed to be the candidate gene. Here we present molecular analysis of the RPS19 gene in DBA patients from the Czech National DBA Registry. We found that the RPS19 gene was mutated in 25% (5/20) of DBA patients (insertion, deletion, and point mutations, but no nonsense or splice site mutations). Point mutations were localized to hot spots defined by Willig (TN Willig, N Draptchinskaia, I Dianzani, et al. Blood 94:4294-4306, 1999). Moreover, we describe two processed RPS19 pseudogenes, which were not expressed. Possible models of the DBA pathogenesis in the view of RPS19 mutations are discussed.
Keywords: dítě; Base Sequence; molekulární sekvence - údaje; novorozenec; Adolescent; sekvenční seřazení; Fanconiho anemie; předškolní dítě; lidé; Adult; Molecular Sequence Data; dospělí; kojenec; Female; Mutation; Pseudogenes; sekvence aminokyselin; mutace; Amino Acid Sequence; Male; ženské pohlaví; ribozomální proteiny; Sequence Alignment; Fanconi Anemia; Child; Humans; mužské pohlaví; Ribosomal Proteins; pseudogeny; Infant, Newborn; Infant; Child, Preschool; sekvence nukleotidů; mladiství